2021
DOI: 10.7759/cureus.13267
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Aspiration Getting Weird: Crack Pipe Aspiration

Abstract: Bulathsinghala et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Steel wool products are not designed to be used as screens for smoking drugs, and they are more likely to disintegrate faster when being handled and inserted into the stem and heated then brass screens, the latter which are distributed by harm reduction programs. When smoking drugs, these steel wool products may break apart into fragments which are then inhaled and can cause injuries to the oral cavity, larynx and lungs [ 7 , 14 18 , 29 34 ]. Several studies reported that negative health consequences associated with using Brillo® for smoking drugs are common among people who use drugs and include: inhaling the whole Brillo® screen, developing burns and cuts on lips, developing cuts on fingers when handling Brillo® and breathing difficulties [ 17 , 20 , 24 , 27 , 33 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Steel wool products are not designed to be used as screens for smoking drugs, and they are more likely to disintegrate faster when being handled and inserted into the stem and heated then brass screens, the latter which are distributed by harm reduction programs. When smoking drugs, these steel wool products may break apart into fragments which are then inhaled and can cause injuries to the oral cavity, larynx and lungs [ 7 , 14 18 , 29 34 ]. Several studies reported that negative health consequences associated with using Brillo® for smoking drugs are common among people who use drugs and include: inhaling the whole Brillo® screen, developing burns and cuts on lips, developing cuts on fingers when handling Brillo® and breathing difficulties [ 17 , 20 , 24 , 27 , 33 , 35 ].…”
Section: Introductionmentioning
confidence: 99%